Management of oral focal infection in patients with asthmatic symptoms - Haryono Utomo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Asthma is commonly related to allergic diseases, nevertheless only 40% of asthma patients are related to allergy or atopy. There are some unknown etiologies of asthma that are still in researches. One of the possible causes of asthma is the multiple chemical sensitivity syndrome (MCS) which related to the “neurogenic switching hypothesis”. Since rhinitis, sinusitis and asthma are closely related, treatments which are successfully reduce or eliminate the rhinitis and sinusitis symptoms should also be advantageous to asthma management. There were a lot of sinusitis treatments which reduced asthma symptoms such as nasal corticosteroid, diathermy and surgery. It was also been reported that oral focal infection might cause sinusitis. However, the involvement of oral focal infection in the etiopathogenesis of asthma was seldom discussed. The objective of this study is to propose a mechanism of the relationship between oral focal infection and asthma which is explained by the “neurogenic switching hypothesis”. Two asthmatic patients who also had periodontal disease, pulpal and periapical infection were treated with conventional and/or surgical dental treatments. After the dental and periodontal treatments were completed, the usual triggers of severe asthma attacks such as cold and house dust did not elicit the asthma symptoms. It concluded that regarding to the disappearing of asthma symptoms, the elimination of oral focal infection had a beneficial effect in reducing asthma symptoms.